READING MISCUE ANALYSIS: A COMPARATIVE STUDY OF TWO GROUPS FROM THIRD SEMESTER STUDENTS IN STUDY PROGRAM OF ENGLISH UNIVERSITAS BRAWIJAYA - PURWANDANIK, NURINTAN (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Reading, Miscue Analysis, Retrospective Miscue Analysis (RMA),Good Readers, Poor Readers. Reading is one of basic human skills beside listening, speaking, and writing which functions for helping people to gain new information. Miscue Analysis is a method which attempt to analyze the unexpected responses of unfamiliar text which occurs in oral reading. Retrospective Miscue Analysis (RMA) was used in this study by comprising reading text aloud, retelling and discussion session. These steps helped the readers develop their reading skills. This study was conducted to find out the answer to what the oral reading miscue types are produced by the good and poor readers from third semester students in Study Program of English Universitas Brawijaya and what the factors are contributing the miscue production.In achieving the purposes of the study, the writer applied theories of Types of Miscue (Goodman and Burke, 1973), Three Cueing Systems (Goodman, 1969), and Factors Contributing Miscues Production (Kern, 1988). The data were originated from all utterances of six participants divided into two groups encompass good readers group and poor readers group. The data were taken by recording process, and they were transcribed into transcription.The results showed the good readers group made 23 (47%) omissions, 9 (19%) substitutions, 7 (14%) insertions, 6 (12%) self-repetitions, and 4 (8%) repetitions. Then, the results of factors contributing miscues production showed the two students were influenced by linguistic and affective factor. Meanwhile, one student was influenced by linguistic, affective, and cognitive factor. Besides, the poor readers group made 87 (44%) omissions, 49 (25%) substitutions, 33 (17%) repetitions, 19 (10%) self-corrections, and 8 (4%) insertions. Moreover, the results of factors indicating miscue production showed linguistic, affective, and cognitive factor were the three factors contributing miscue production of the three students. The result of the study showed that the good readers and poor readers made miscues in their oral reading, although the good readers made fewer miscues than the poor readers.The writer suggests for the further writer who wants to conduct a study in the same field of RMA to use different subjects and instruments. Then, the writer suggests for the lecturers to develop their strategy of teaching reading for the students.